Joint interference management and resource allocation for device-to-device (D2D) communications underlying downlink/uplink decoupled (DUDe) heterogeneous networks - Celik, Abdulkadir; Radaydeh, Redha M.; Al-Qahtani, Fawaz S.; Alouini, Mohamed-Slim (IEEE International Conference on Communications (2003), 2017)
In this paper, resource allocation and co-tier/cross-tier interference management are investigated for D2D-enabled heterogeneous networks (HetNets) where tiers 1, 2, and 3 consist of macrocells, smallcells, and D2D pairs, respectively. We first propose a D2D-enabled fractional frequency reuse scheme for uplink (UL) HetNets where macrocell subregions are preassigned to different subbands (SBs) in order to mitigate the tier-1↔tier-1 interference. Nevertheless, cell-edge macrocell user equipments (MUEs) with high transmission powers still form dead-zones for nearby smallcell UEs (SUEs) and D2D UEs (DUEs). One of the simple but yet novel means of the dead-zone alleviation is associating the cell-edge MUEs with nearby smallcells, which is also known as downlink (DL)/UL decoupling (DUDe). Subject to quality of service (QoS) requirements and power constraints, we formulate a joint SB assignment and resource block (RB) allocation optimization as a mixed integer non-linear programming (MINLP) problem to maximize the D2D sum rate and minimize the co-tier/cross-tier interference. Based on tolerable interference limit, we propose a fast yet high-performance suboptimal solution to jointly assign available SBs and RBs to smallcells. A D2D mode selection and resource allocation framework is then developed for DUEs. As traditional DL/UL Coupled (DUCo) scheme generates significant interference proportional to cellular user density and user association bias factor, results obtained from the combination of proposed methods and developed algorithms reveal the potential of DUDe for co-tier/cross-tier interference mitigation which opens more room for spectrum reuse of DUEs.